Phototherapy in different stages of birth weight for the treatment of neonatal hyperbilirubinaemia - Paul, T; Parial, R; Hasem, MA; Mojumder, S; Islam, MM; Junaid, MM; Das, M; Alauddin, M (Journal of Bio-Science, 2011)
Context: The goal of phototherapy is to lower the concentration of circulating bilirubin or keep it from increasing in the treatment of neonatal unconjugated hyperbilirubinaemia. As phototherapy decrease billirubin level of infants, it is important to fix the dose of phototherapy. Objectives: The aim of the study was to compare the effectiveness of double phototherapy versus conventional single phototherapy in the treatment of neonatal unconjugated hyperbilirubinaemia. Materials and Methods: For this purpose 50 term and preterm newborns were enrolled. They were divided into 2 groups, 38 newborns were taken in group 1 and 12 newborn were taken in group 2. The babies who got conventional single phototherapy were taken in group 1. Each group was again divided into 3 subgroups according to their birth weight Normal Birth Weight (NBW), = Low Birth Weight (LBW) and Very Low Birth Weight (VLBW). Results: The serum bilirubin level of term babies were found 17.32 ± 4.08 mg/dl and in preterm babies were found 13.17 ± 1.49 mg/dl. Neonatal hyperbilirubinaemia in enrolled babies were due to physiologic jaundice (38%), neonatal sepsis (50%) and perinatal asphyxia (12%). The serum bilirubin level in physiological jaundice was found 18.47 ± 5.38 mg/dl, in neonatal sepsis was found 14.90 ± 1.85 mg/dl and in perenatal asphyxia was found 14.10 ± 1.47 mg / dl. Decline rate of serum bilirubin per day was found 4.58 ± 2.43 mg / dl in NBW babies with the use of conventional single phototherapy compared to 6.27 ± 2.26 mg / dl with the use of conventional double phototherapy. In LBW babies decline rate of serum bilirubin per day was found 2.07 ± 0.84 mg / dl with the use of conventional single phototherapy but 4.70 ± 2.08 mg / dl with the use of conventional double phototherapy. In VLBW babies, decline rate of serum bilirubin per day was found 2.24 ± 1.10 mg / dl with the use of conventional single phototherapy. Any VLBW babies which were given conventional double phototherapy were not found. Conclusion: From this study it can be concluded that double phototherapy is more effective than conventional single phototherapy in the treatment of neonatal hyperbilirubinaemia in both groups of neonates; however the rate of fall of bilirubin was higher in NBW subgroups. Keywords: Phototherapy; hyperbilirubinaemia; preterm; term. DOI: http://dx.doi.org/10.3329/jbs.v18i0.8786 JBS 2010; 18(0): 116-120